Verification of universal surface scaling behavior in critical binary liquid mixtures with neutron and x-ray reflectometry - Brown, Matthew D. (Kansas State University, 2007)
We have studied two critical binary liquid mixtures in the mixed phase regime with x-ray and neutron reflectometry to verify universal critical scaling at a non-critical interface. We compared our results with previous results obtained with ellipsometry. At a solid-liquid or liquid-vapor interface of an AB binary liquid mixture the component with the lower surface tension will dominate that interface. If the surface tension differential between the components of the mixture is large enough the composition of the surface layer will loose its dependence on. This case is referred to as strong adsorption. We study the case of strong adsorption for a binary liquid mixture at the critical composition with respect to the demixing phase transition. Sufficiently close to the critical temperature Tc the influence of bulk critical behavior is expected to dominate the way the surface adsorption layer decays with depth z from the surface composition to the bulk composition. The length scale of the decay profile is expected to be proportional to the composition correlation length, and is expected to scale with a universal composition scaling function. In a neutron reflectometry study of a critical mixture of D2O and 3-methylpyridine against a quartz substrate we verify universal critical scaling using a scaling function previously used to describe ellipsometry data. In an x-ray reflectometry study of the liquid-vapor interface of a critical mixture of n-dodecane and 1,1,2,2 tetrabromoethane, which had previously been studied with ellipsometry, we find that we are able to describe all data by using the same scaling function provided that we account for non-critical, system dependent surface structure as well. We are also able to simulate ellipsometry with our mathematical profile model and compare the simulation to the previous ellipsometry data.
Keywords: reflectometry; ellipsometry; critical; binary; neutron; scaling; Physics, Condensed Matter (0611)